2013
DOI: 10.1111/liv.12263
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid system in advanced liver cirrhosis: pathophysiological implication and future perspectives

Abstract: Endogenous cannabinoids (EC) are ubiquitous lipid signalling molecules providing different central and peripheral effects that are mediated mostly by the specific receptors CB1 and CB2. The EC system is highly upregulated during chronic liver disease and consistent experimental and clinical findings indicate that it plays a role in the pathogenesis of liver fibrosis and fatty liver disease associated with obesity, alcohol abuse and hepatitis C. Furthermore, a considerable number of studies have shown that EC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 100 publications
1
49
1
Order By: Relevance
“…70,71 The same study also observed an inhibition of the activated hepatic endocannabinoid system in ciprofloxacin-treated cirrhotic animals, which enhanced the concepts of endotoxemia and activate hepatic endocannabinoid system in cirrhosis. 11,58,70 Actually, chronic administration of the cannabinoid receptor antagonist inhibits the hepatic inflammation and fibrogenesis in cirrhotic animals. 9,63 However, increased hepatic endocannabinoid production enhanced the hepatic vasoconstrictive response to ET-1 and subsequently increased IHR and portal hypertension in nonalcoholic steatohepatitis (NASH)-cirrhotic rats.…”
Section: (4) Endocannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 The same study also observed an inhibition of the activated hepatic endocannabinoid system in ciprofloxacin-treated cirrhotic animals, which enhanced the concepts of endotoxemia and activate hepatic endocannabinoid system in cirrhosis. 11,58,70 Actually, chronic administration of the cannabinoid receptor antagonist inhibits the hepatic inflammation and fibrogenesis in cirrhotic animals. 9,63 However, increased hepatic endocannabinoid production enhanced the hepatic vasoconstrictive response to ET-1 and subsequently increased IHR and portal hypertension in nonalcoholic steatohepatitis (NASH)-cirrhotic rats.…”
Section: (4) Endocannabinoidsmentioning
confidence: 99%
“…cirrhosis. 11,58,70 HED is characterized by an increased pressure response to vasoconstrictors including endocannabinoids in hepatic microvasculatures. 40,41,48,49 Chronic administration of ciprofloxacin had also been found to inhibit endotoxemia, improve HED, and decrease IHR in cirrhotic animals.…”
Section: (4) Endocannabinoidsmentioning
confidence: 99%
“…CB1 agonists activate hepatic stellate cells to myofibroblasts. CB1 receptor agonists, such as Rimonabant, inhibit and reverse experimental liver fibrosis [43][44]. A peripherally acting CB1 antagonist could treat liver fibrosis without inducing depression.…”
Section: Promotion Of Apoptosis Of Activated Hscsmentioning
confidence: 99%
“…Apart from CB1, other receptors, such as TRPV1, may be implicated in the EC-dependent vasorelaxation of liver cirrhosis. TRPV1, expressed in perivascular nerves, has been shown to mediate the hypotensive effect of EC in cirrhosis [65]. Moreover, it has been shown that in cirrhotic rats pretreatment with a molecule blocking the response of sensory nerves impairs the mesenteric artery vasorelaxation induced by anandamide, suggesting that the signaling pathway leading to relaxation is located in the adventitia of the vessels, where primary sensory nerves are situated.…”
Section: Increased Circulating Vasodilatorsmentioning
confidence: 99%